The Role of Management Information Systems in the Aviation Industry on the Batik Air App - Dewi Puspaningtyas Faeni; Amelia Putri (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study discusses the role of management information systems (MIS) in the aviation industry on the Batik Air application. In the aviation industry, MIS plays an important role in improving efficiency and service quality. Batik Air, as one of Indonesia's domestic airlines, has a need to improve service quality and increase passenger satisfaction. In this study, researchers used a qualitative research method with a literature study approach to analyze the role of management information systems (MIS) in the aviation industry on the Batik Air application. The results of the study show that it is very important to have a useful MIS in the modern era like today, because of the increasingly tight competition. If we have a MIS in online flight services, Batik Air supports people in their daily lives, especially for purchasing tickets via the internet. By using the Batik Air Mobile App, ordering tickets online has many advantages, but also has disadvantages.